Javanese Stories of Jesus - Wasim, Alef Theria; Steenbrink, Karel (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2005)
The Jesus-section of the JavaneseÂ Serat Anbiya starts at the end of the story of the People of the Cave, the Muslim version of the Christian legend of the Seven Sleepers of Ephesos, who fled persecution under Emperor Decius (249-251) and disappeared, until they were found and rose up again. In most versions of this series, this story is told after the Jesus section (in Tha'labi, Rabghuzi, Mirkhond, but not in Kisai), but here it precedes the Jesus-story.DOI:Â 10.15408/sdi.v12i2.589